The conglomerate discount in Germany and the relationship to corporate governance - Christian Weiner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper documents the conglomerate discount for all available German firms and the DAX 30 firms in detail. It shows a moderate discount of about 0.06 based on German comparable firms and of about 0.20 for a combined sample of German and European peer groups. I further examine the relationship between the discount and industry concentration as well as uncertainty of valuation. Finally, I document that corporate governance behavior affects the conglomerate discount.
Keywords: 330